Readiness Of Students Who Use Learning Contracts On Ante Natal Care Practice in Third Trimester - Nurul Komariah; Lily Novianti (Poltekkes Kemenkes Palembang, 2022)
Midwives as one of the oldest professions in the world have a very important and strategic role in reducing Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). Midwives must have clinical competence (midwifery skills), one of which is pregnancy examination. Clinical competence is obtained from clinical learning. Good clinical learning is one that is planned, one of which is using a learning contract. The purpose of the study was to determine the readiness of students who use learning contracts to carry out pregnancy tests in the third trimester. The research design is descriptive. The research sample is all fourth semester students of the Midwifery Study Program who have practiced in the Practical Field in 2019. The number of samples is 80 people. The sampling method is total sampling. The instrument used is an open ended question. Data analysis is univariate. Frequency distribution. The results are 87% optimal physical readiness, maximum 7.2%, 1.4% less. Emotional readiness 65.2% optimal, 10.1% maximum. Knowledge readiness 87% optimal, 11.6% maximum. In conclusion, more than half of practicing contract users learn that they have optimal readiness. The best readiness is the readiness of knowledge